The relationship between total quality management and innovation in the South African foundry/steel industry - Toga, Mainford (My University, 2017)
In today’s global economic environment, companies have to deal with strong global competition, fast technological changes, and shortage of resources; therefore, they need to innovate to produce competitive products or services in order to survive. Total quality management strives to create a culture of ‘doing it right the first time’ by designing and building quality into each activity, rather than inspecting quality in the final products. Most organisations have therefore implemented TQM practices in order to produce quality products and enhance their competitiveness. Innovation and TQM are regarded as the key drivers of competitiveness in business. Therefore a study on the link between TQM and innovation is of paramount importance, and although a number such studies were done in Europe, North America and Asia, no evidence is there for studies in Africa. As such, this thesis sought to contribute to the understanding of the relationship between TQM dimensions of customer focus, leadership and people management with the product and process forms of innovation in the South African Foundry industry. A quantitative research approach was used to collect data from the South African Foundry industry and a low response rate of 83 respondents obtained. The hierarchical multiple regression analysis was used to study the relationship, with firm size and period since initial certification with a quality management system as the control variables. The results revealed that customer focus, leadership and people management were all positively related to product innovation while only people management was positively related to process innovation. Though the R2 values explained less than 10% of the relationship, the results were statistically significant and underlines the importance of TQM in both quality and innovation fields. Certification was found to be negatively associated with process innovation while firm size played no role in both product and process innovations.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation Johannesburg, 2017